2017
DOI: 10.1021/acs.analchem.7b02608
|View full text |Cite
|
Sign up to set email alerts
|

Visual, Label-Free Telomerase Activity Monitor via Enzymatic Etching of Gold Nanorods

Abstract: Early diagnosis and life-long surveillance are clinically important to improve the long-term survival of cancer patients. Telomerase activity is a valuable biomarker for cancer diagnosis, but its measurement often used complex label procedures. Herein, we designed a novel, simple, visual and label-free method for telomerase detection by using enzymatic etching of gold nanorods (GNRs). First, repeating (TTAGGG) sequences were extented on telomerase substrate (TS) primer. It formed G-quadruplex under the help of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…To date, different metal nanoparticles, such as gold nanospheres, gold nanorods, silver nanospheres, silver nanoprisms, core/shell Au@Ag nanospheres, and core/shell Au@Ag nanorods, have been used as etching-based plasmonic sensors. Etching-based plasmonic sensors incorporating these nanoparticles have been used to detect various targets including DNA, (Ma et al, 2016;Malile and Chen, 2013;Yang et al, 2014) proteins, (Cheng et al, 2016;Guo et al, 2016b;Liang et al, 2015a;Lu et al, 2016;Yang et al, 2017;Zhang et al, 2015b;Zhao et al, 2016) metal ions, (Chang et al, 2017;Chemnasiri and Hernandez, 2012;Chen et al, 2016bChen et al, , 2016cChen et al, , 2009Chen et al, , 2013bJin and Han, 2014;Lan and Lin, 2014;Liu et al, 2013c;Wang et al, 2014;Yao et al, 2017;Zhang et al, 2014aZhang et al, , 2014bZhu et al, 2016) anions, (Chen et al, 2015(Chen et al, , 2012bHe and Yu, 2015;Li et al, 2011Li et al, , 2015Liu et al, 2013a;Sasikumar and Ilanchelian, 2017;Tripathy et al, 2011;Xin et al, 2012;Zeng et al, 2014;Zhang et al, 2015aZhang et al, , 2016 and glucose, (Jang and Min, 2015;Lin et al, 2016;…”
Section: Plasmonic Colorimetric Sensors Using Metal Nanoparticle Etchingmentioning
confidence: 99%
“…To date, different metal nanoparticles, such as gold nanospheres, gold nanorods, silver nanospheres, silver nanoprisms, core/shell Au@Ag nanospheres, and core/shell Au@Ag nanorods, have been used as etching-based plasmonic sensors. Etching-based plasmonic sensors incorporating these nanoparticles have been used to detect various targets including DNA, (Ma et al, 2016;Malile and Chen, 2013;Yang et al, 2014) proteins, (Cheng et al, 2016;Guo et al, 2016b;Liang et al, 2015a;Lu et al, 2016;Yang et al, 2017;Zhang et al, 2015b;Zhao et al, 2016) metal ions, (Chang et al, 2017;Chemnasiri and Hernandez, 2012;Chen et al, 2016bChen et al, , 2016cChen et al, , 2009Chen et al, , 2013bJin and Han, 2014;Lan and Lin, 2014;Liu et al, 2013c;Wang et al, 2014;Yao et al, 2017;Zhang et al, 2014aZhang et al, , 2014bZhu et al, 2016) anions, (Chen et al, 2015(Chen et al, , 2012bHe and Yu, 2015;Li et al, 2011Li et al, , 2015Liu et al, 2013a;Sasikumar and Ilanchelian, 2017;Tripathy et al, 2011;Xin et al, 2012;Zeng et al, 2014;Zhang et al, 2015aZhang et al, , 2016 and glucose, (Jang and Min, 2015;Lin et al, 2016;…”
Section: Plasmonic Colorimetric Sensors Using Metal Nanoparticle Etchingmentioning
confidence: 99%
“…The detection limit for telomerase and PARP-1 was 13 cells per mL and 0.02 U, respectively. Compared with the previously reported methods for telomerase detection listed in Table 1, it can be concluded that this method is more sensitive than the UV methods 6,43. It is also comparable to other sensitive methods such as ECL,40ā€“47 CL,9 SERS,48 and fluorescence methods that use other probes 49ā€“53.…”
Section: Resultsmentioning
confidence: 65%
“…First, the extended primer is a powerful displacement strand that can be used to initiate the signal ā€œturn-onā€ or ā€œturn-offā€ based on the hybridization of DNA 3ā€“5. Second, the extended G-rich primer forms a G-quadruplex, which has high peroxidase-like activity and can initiate signals closely related to the catalyzed reaction 6ā€“9. Third, the extended DNA sequence has ample negative charges that have great influence on the signal depending on the electrostatic interactions 10ā€“12.…”
Section: Introductionmentioning
confidence: 99%
“…The limit of detection of this method was found to be 0.006 ng for a single application and 0.012 ng for five test sample analysis [29]. Recently Yang, et al have developed gold nano rods (AuNRds) based monitoring of telomerase activity, which is a valuable marker for cancer diagnosis [30]. This strategy was a simple, naked eye based detection and label free method for telomerase sensing through enzymatic etching of AuNRds.…”
mentioning
confidence: 99%
“…where ATP (Adenosine triphosphate) was shown to enhance the peroxidase-like activity of citrate-stabilized AuNPs. Different sized of AuNPs (15,30,50 and 70 nm) were studied, of which 30 nm exhibited synergistic peroxidase-like activity in presence of ATP. Further, the catalytic activity was found unaltered when the reaction was performed in presence of ADP, free phosphate, sulphate and carbonate anions, however, addition of ascorbic acid diminished the intrinsic peroxidase-like activity, even in the presence of ATP.…”
mentioning
confidence: 99%